Air pollution and possible risk of dementia in the Czech Republic - Topinka J; Rossner P; Rossnerova A; Sram RJ (Journal of Biology and Medicine - Peertechz Publications, 2022)
A review of recent literature indicates a significant effect of air pollution on the increased incidence of dementia, particularly Alzheimer's disease. A possible mechanism is related to oxidative damage and inflammation. In the Czech Republic in previous decades the mining districts of Northern Bohemia suffered from very high air pollution levels, while during the last period in Northern Moravia this problem was also noted. This specific situation could be used to study the impact of air pollution on dementia, using new methods of molecular epidemiology together with the complex analysis of the lifestyle of the population living in the polluted regions.